Batik, Lengkeng, Zat Warna Alam PEMANFAATAN DAUN LENGKENG (Nephelium Logan) UNTUK PEWARNA BATIK - Amantika, Ravika Setyo; Syamwil, Rodia; Nurrohmah, Siti (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2021)
UTILIZATION OF LEAF LITCHI (NEPHELIUM LOGAN) FOR BATIK DYES. Abstract : The purpose of this study to determine whether the leaves litchi can be used as natural dye for batik cloth. This research uses experimental method and the result in laboratory test to see the quality of dyeing result with leaf litchi. The analysis used that is analysis descriptive on all results test laboratory . The object of this research is leaf litchi , primissima mori cloth that has been batik, type mordan (alum, lime tohor, tunjung). Leaf extraction process litchi with type different mordant showing existence difference old age color on fabric morri that is without mordan produce most young color with value the mean T% 44,32, with alum with value the mean T% 46,71, then chalk with value the mean T% 77.79, and tunjung produce The oldest color with value average of TT% 94.02. Conclusions can be explained that leaf litchi can be used as a source of natural dyes in bati k and the type of mordan used can affect the direction of the resulting batik color Keywords: Batik, Leaf litchi (Nephelium logan) , Natural Color Substance